Melamine regulatory assessment for endocrine disruption - Isabelle Charron; Brigitte Le Magueresse-Battistoni; René Habert; Marie-Chantal Canivenc-Lavier; Sakina Mhaouty-Kodja; Cécile Michel-Caillet (Environment International)
Melamine has several domestic and industrial uses as a flame retardant or in the manufacture of melamine–formaldehyde resins. Based on available scientific literature data, the French Agency for Food, Environmental and Occupational Health & Safety (ANSES) included this substance in the list of “chemicals that may present endocrine disruptor (ED) properties”, and the substance was prioritized to assess whether it should be classified as an ED in European Union (EU) regulations for hazard identification. This review reports the assessment of melamine based on relevant studies from the registration dossier under REACH, and peer-reviewed literature. Among the various adverse effects, reproductive, neurodevelopmental, and thyroid effects were analyzed in particular, because they could be the consequence of an endocrine disruption. The different modes of action (endocrine or non-endocrine) potentially leading to these effects were scrutinized to understand whether the WHO definition for ED and the criteria for hazard identification were met. It was concluded that the reproductive effect on spermatogenesis was not a consequence of endocrine activity. A biologically plausible link between this effect and endocrine activity was not established, and other modes of action (oxidative stress or altered energy metabolism) could be involved. Similarly, thyroid and neurodevelopmental effects appeared at higher doses than those leading to renal toxicity. Our assessment confirms that melamine is a reprotoxic substance but does not support ED classification. This assessment illustrates the scientific and regulatory challenges in differentiating specific endocrine disruption from an indirect endocrine effect resulting from non-ED mediated systemic toxicity.